From Bench to Bedside: Implications of Lipid Nanoparticle Carrier Reactogenicity for Advancing Nucleic Acid Therapeutics - Tetiana Korzun; Abraham S. Moses; Parham Diba; Ariana L. Sattler; Olena R. Taratula; Gaurav Sahay; Oleh Taratula; Daniel L. Marks (MDPI AG, 2023)
In biomedical applications, nanomaterial-based delivery vehicles, such as lipid nanoparticles, have emerged as promising instruments for improving the solubility, stability, and encapsulation of various payloads. This article provides a formal review focusing on the reactogenicity of empty lipid nanoparticles used as delivery vehicles, specifically emphasizing their application in mRNA-based therapies. Reactogenicity refers to the adverse immune responses triggered by xenobiotics, including administered lipid nanoparticles, which can lead to undesirable therapeutic outcomes. The key components of lipid nanoparticles, which include ionizable lipids and PEG-lipids, have been identified as significant contributors to their reactogenicity. Therefore, understanding the relationship between lipid nanoparticles, their structural constituents, cytokine production, and resultant reactogenic outcomes is essential to ensure the safe and effective application of lipid nanoparticles in mRNA-based therapies. Although efforts have been made to minimize these adverse reactions, further research and standardization are imperative. By closely monitoring cytokine profiles and assessing reactogenic manifestations through preclinical and clinical studies, researchers can gain valuable insights into the reactogenic effects of lipid nanoparticles and develop strategies to mitigate undesirable reactions. This comprehensive review underscores the importance of investigating lipid nanoparticle reactogenicity and its implications for the development of mRNA-lipid nanoparticle therapeutics in various applications beyond vaccine development.